2015
DOI: 10.1007/s12539-015-0283-8
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Study of Variable Surface Proteins in Plasmodium Species: Perspectives in Drug Design

Abstract: The variable surface proteins expressed by P. falciparum and P. vivax are transported to the surface of infected erythrocyte and are exposed to the host immune system. The possibility of using variable surface proteins as a common drug target has been analyzed in both the Plasmodium species. Sequence analysis of variable surface proteins showed a low-level conservation within as well as between the species. Amino acid composition analysis revealed higher frequency of hydrophilic amino acids as compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Moreover, in vitro, both hemozoin and soluble P. falciparum antigens (sPfAg) are capable of inducing BAFF release from monocytes and B‐cell co‐cultures . Within this context, it must be evoked that P. falciparum and P. vivax are genetically distant malaria parasites . Probably the heterogeneity between the two species, such as in its chemical composition of soluble antigens and hemozoin could differently modulate BAFF and APRIL production as well as cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in vitro, both hemozoin and soluble P. falciparum antigens (sPfAg) are capable of inducing BAFF release from monocytes and B‐cell co‐cultures . Within this context, it must be evoked that P. falciparum and P. vivax are genetically distant malaria parasites . Probably the heterogeneity between the two species, such as in its chemical composition of soluble antigens and hemozoin could differently modulate BAFF and APRIL production as well as cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, it must be evoked that P. falciparum and P. vivax are genetically distant malaria parasites . Probably the heterogeneity between the two species, such as in its chemical composition of soluble antigens and hemozoin could differently modulate BAFF and APRIL production as well as cytokines. Indeed, our findings showed that, in P. vivax acute phase malaria, APRIL but not BAFF levels correlated positively with IL‐1, IL‐2, IL‐4, IL‐6, and IL‐13 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymes from both strains exhibited the optimal pH for enzyme catalysis, at pH 7.5, and were stable at temperatures below 60 degrees C. They therefore proposed that GSTs from both malarial strains are identical in their functional domain but different in level of gene expression (Harwaldt et al, 2002;Al-Qattan et al, 2016). Yadav MK et al analysed the possibility of using variable surface proteins as a common drug target in both the Plasmodium species (Yadav and Swati, 2016). Sequence analysis of variable surface proteins showed a low-level conservation within as well as between the species.…”
Section: Discussionmentioning
confidence: 99%
“…Structural alignment of variable surface proteins by superimposing them showed less conservation. The noted existence of structural differences showed that the variable surface proteins could not be used as a common drug target in both the malarial species (Yadav and Swati, 2016). The authors concluded that species-speci ic strategy may be followed for drug targeting against variable surface proteins of P. falciparum and P. vivax.…”
Section: Discussionmentioning
confidence: 99%